Configurations of Young Peoples' Important Life Goals and Their Associations with Thriving. Issue 2 (3rd April 2018) - Johnson, Sara K.; Tirrell, Jonathan M.; Schmid Callina, Kristina; Weiner, Michelle B.
Abstract : The aims of this study were to determine whether, and how, young people's beyond-the-self life goals coexisted with other life goals, and whether having at least one beyond-the-self goal was associated with higher thriving (the Five Cs of Positive Youth Development [PYD]) and volunteering, compared to having either no goals, or goals that were only self-focused. The authors conducted latent class analyses among five school cohort groups using data from five studies (combined using integrative data analysis techniques). Across grade groups, the authors identified classes, which can generally be characterized by (1) low endorsement of goals, (2) prominence of helping others and contributing to community goals, (3) prominence of goals related to a good life (e.g., make money, friends, live an adventurous life), and (4) endorsement of most life goals. In the older two grade groups we identified additional classes: a group with a high endorsement of goals oriented at helping others and serving God/higher power in the undergraduate group, and a group with high endorsement of goals to create something new and make the world a better place in the graduate group. There were differences in the Five Cs of PYD and volunteering between the classes. The authors discuss the implications of these results for future research and practice regarding young people's life goals.